Development of hot stamping tool by using indirect hot stamping for basic bending part (u-shape) - Mohd Fawzi, Zamri; A. R., Yusoff (2014)

(untitled)
In hot stamping process, (UHSS) blank was cut into the rough shape. The blank is then heated to the temperature (900 - 950 °C) for 5 to 10 minutes inside the furnace. Then, the blank must be transferred quickly to the press to avoid the part is cooled before forming. After that, the blank is formed and cooled simultaneously by the water cooled die for 5 to lOs. Due to the contact between hot blank and the cool tool, the blank is cooled in the closed tool [1]. Today, hot stamping exists in two different types of methods which are direct and indirect. For indirect hot stamping method, before the blank is heated inside the furnace, it then undergoes cold pre-forming process. This process is done once after the blank is cut.